Novel Amino Acid Derivatives of Quinolines as Potential Antibacterial and Fluorophore Agents - Oussama Moussaoui; Rajendra Bhadane; Riham Sghyar; El Mestafa El Hadrami; Soukaina El Amrani; Abdeslem Ben Tama; Youssef Kandri Rodi; Said Chakroune; Outi M. H. Salo-Ahen (MDPI AG, 2020)
A new series of amino acid derivatives of quinolines was synthesized through the hydrolysis of amino acid methyl esters of quinoline carboxamides with alkali hydroxide. The compounds were purified on silica gel by column chromatography and further characterized by TLC, NMR and ESI-TOF mass spectrometry. All compounds were screened for in vitro antimicrobial activity against different bacterial strains using the microdilution method. Most of the synthesized amino acid-quinolines show more potent or equipotent inhibitory action against the tested bacteria than their correspond esters. In addition, many of them exhibit fluorescent properties and could possibly be utilized as fluorophores. Molecular docking and simulation studies of the compounds at putative bacterial target enzymes suggest that the antimicrobial potency of these synthesized analogues could be due to enzyme inhibition via their favorable binding at the fluoroquinolone binding site at the GyrA subunit of DNA gyrase and/or the ParC subunit of topoisomerase-IV.